Bricks & brickmaking - Hammett, Michael; Brown, Stephen; Marshall, Duncan; The Brick Development Association (Bristol : UWE Bristol ; New York, NY : Distributed by Insight Media, 2001)
This film shows sequences from representative contemporary brickworks. It shows how clay bricks are formed by handmaking, machine moulding, pressing and extrusion, and shows how they are fired in traditional clamps, intermittent kilns and continuous-burning multi-chamber and tunnel kilns
Title from title screen
DVD format
Keywords: Brickmaking; Kilns; Bricks